Current levels, composition profiles, source identification and potentially ecological risks of polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in the surface sediments from Bohai Sea. Issue 2 (30th December 2015) - Wang, Guoguang; Peng, Jialin; Yang, Dandan; Zhang, Dahai; Li, Xianguo
Abstract: Polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) were analyzed to assess the environmental quality in the surface sediments from Bohai Sea (BS), China. Concentrations of ∑37 PCBs, ∑7 PBDEs and BDE-209 were 0.157–1.699, 0.100–0.479 and 0.464–6.438 ng/g (dry weight), respectively. All of these concentrations decreased generally from the coastal areas towards the outer sea, indicating intensive influences of anthropogenic activities. Principal component analysis (PCA) coupled with multiple linear regression (MLR) revealed that 82.1% of the PCBs in BS came from direct discharge of local anthropogenic activities, 16.3% from surface runoff of contaminated soils and 1.6% from atmospheric deposition. PBDEs were mainly derived from the usage and dismantling of products containing commercial Penta-, Octa- and Deca-BDEs. According to sediment quality guidelines (SQGs), the ecological risks of PCBs could be negligible, and penta- and deca-BDE homologs might be the major contributors of ecological risks in the BS sediments. Highlights: PCB and PBDE levels showed decreasing gradient from coastal areas to outer sea. PCBs came from local human activities, surface runoff and atmospheric deposition. PBDEs mainly originated from commercial Penta-, Octa- and Deca-BDEs in BS. Penta- and deca-BDE homologs were major contributors of ecological risks in BS.